Análise dos fatores que influenciam a produtividade do rebanho leiteiro na Zona da Mata, Minas Gerais - Nascimento da Cunha, José Antônio; Coelho de Alvarenga, Sonia; Batista de Oliveira, Evonir; Teixeira Gomes, Sebastião; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
This study attempts to identify and analyze factors which affect productivity in milk production in the Zona da Mata, in the State of Minas Gerais.